(untitled) (Experimental biology, 2021)
The article presents the results of the first stage of three-year (2018-2020) studies of a rare, poorly studied species with the Jungarian-Himalayan type of range Hepatica falconeri (Toms.) Steward. from the family Ranunculaceae Juss. The analysis of own research of literature data and herbarium specimens held in the collections of the Kazakh national University named after al-Farabi, Institute of botany and Phytointroduction, MES RK, as well as site data of the Herbarium of Moscow University (http://herba.msu.ru) and Plantarium (https://www.plantarium.ru) refined the species distribution and made a point map of the area within Kazakhstan. The result details of the route-reconnaissance survey the territory of the SNNP "Kolsai lakes" the habitat of the largest populations of Hepatica falconeri in the Taldy river valley, which is described in detail in 6 isolated sections. Taking into account modern phylogenetic and taxonomic studies of various authors, the systematic position of the species in the angiosperm system was determined in accordance with the interpretation of A. L. Takhtajyan (1987). As a result of the research, the authors were able to Supplement the ecological characteristics of the species. It is established that it is typical not only for the subalpine belt, as indicated in most literature sources, but descends almost to the lower border of the forest belt (1690 m), which allows us to refer to 2 ecological-cenotic groups – forest and petro-lithophilic. Key words: rare species, genus, family, range, ecology, exposition, Hepatica falconeri, state national nature park (SNNP).